Relationship Between Intraocular Pressure-Lowering Effects and Alterations in Anterior Segment Scleral Birefringence Following Micropulse Cyclophotocoagulation - Nemoto H; Honjo M; Okamoto M; Tominaga S; Yamanari M; Aoyama Y; Arai T; Ishiyama Y; Sugimoto K; Sakata R; Saito H; Fujishiro T; et al. (Clinical Ophthalmology, 2025)
Hotaka Nemoto,1 Megumi Honjo,1 Michiaki Okamoto,2 Sou Tominaga,2 Masahiro Yamanari,2 Yurika Aoyama,1 Takahiro Arai,1 Yukako Ishiyama,1 Koichiro Sugimoto,1 Rei Sakata,1 Hitomi Saito,1 Takashi Fujishiro,1 Makoto Aihara1 1Department of Ophthalmology, University of Tokyo Graduate School of Medicine, Tokyo, Japan; 2Tomey Corporation, Nagoya, JapanCorrespondence: Megumi Honjo, Department of Ophthalmology, University of Tokyo Graduate School of Medicine, 7-3-1 Hongo Bunkyo-ku, Tokyo, 113-8655, Japan, Tel +81-3-3815-5411, Fax +81-3-3817-0798, Email honjomegumi@gmail.comPurpose: To assess the changes in anterior segment scleral birefringence (ASSB), a marker of collagen-related fibrotic responses, following micropulse cyclophotocoagulation (MP-CPC) using polarization-sensitive optical coherence tomography (PS-OCT).Patients and Methods: Eighteen eyes of sixteen patients with glaucoma who underwent MP-CPC at the University of Tokyo Hospital in Japan from July 2022 to August 2023 were included. The procedure utilized a Cyclo G6 glaucoma laser system (IRIDEX, Mountain View, CA, USA) with laser power set at 2,500 mW and an 80-second duration per hemisphere. Clinical outcomes and ASSB were assessed for 6 months. The principal assessment was the evaluation of post-procedure ASSB. Anterior segment images were captured before MP-CPC, and at 1 week, 1 month, 3 months, and 6 months after MP-CPC, using PS-OCT (ROCTIA; Tomey Corporation, Nagoya, Japan) to assess the ASSB. We also assessed the correlation between intraocular pressure (IOP) reduction and changes in birefringence.Results: The IOP was significantly lower after than before MP-CPC (pretreatment: 24.8 ± 1.8, 1 week: 13.9 ± 1.1, 1 month: 17.4 ± 1.1, 3 months: 20.1 ± 1.7, and 6 months: 19.0 ± 1.6 mmHg). ASSB increased significantly after treatment (pretreatment: 1.00 ± 0.08, 1 week: 1.20 ± 0.11, 1 month: 1.27 ± 0.06, 3 months: 1.42 ± 0.07, and 6 months: 1.26 ± 0.15), suggesting post-laser collagen remodeling in the sclera. Notably, a significant positive correlation was found between the rate of IOP reduction and the degree of birefringence elevation at 3 and 6 months post-procedure.Conclusion: We observed a significant increase in ASSB after MP-CPC, and this increase was positively correlated with IOP reduction. These findings point to the potential mechanism underlying IOP reduction and emphasize the clinical relevance of the birefringence value.Keywords: polarization-sensitive optical coherence tomography, PS-OCT, micropulse cyclophotocoagulation, MP-CPC, birefringence